Preferences of Patients With Parkinson's Disease for Communication About Advanced Care Planning. (February 2015) - Tuck, Keiran K.; Brod, Lissa; Nutt, John; Fromme, Erik K.
Background: Despite shortening life, Parkinson's disease (PD) is often not considered "terminal." Uncertainty exists about when to discuss end-of-life planning. Methods: A survey was sent to patients with PD assessing attitudes toward the timing and initiation of discussions regarding their disease. Data were analyzed for patient preferences regarding communication. Results: Of 585 surveys, 267 were returned. Ninety-four percent of patients wanted prognosis and treatment information early. Half of the patients wanted to discuss advanced care documents early. Some wanted early discussions about end-of-life care planning (27%) or end-of-life care options such as hospice (21%). The majority felt shared responsibility for initiating discussions about life expectancy, advance care documents, and end-of-life care planning. Conclusions: Preferences regarding end-of-life discussions vary. Consequently, neurologists should ask patients about their preferences for this information and offer discussion periodically.